Shocks to the lending standards and the macroeconomy - Vivek Sharma (LUISS Guido Carli, Department of Economics and Finance, Arcelli Centre for Monetary and Financial Studies, 2023)
This paper presents a model in which firms have endogenously-persistent lending relationships with banks which compete both on interest rates and collateral requirements. The economy features an endogenously-evolving lending standard which is subject to an exogenous shock. A shock to bank lending standards in this model leads to a spike in spread, drop in bank credit and amplification of macroeconomic volatility. These e↵ects are higher at greater intensity and persistence of the lending relationships. This work shines a spotlight on how shocks to lending standards can have wider macroeconomic implications and shows how financial shocks can a↵ect real economy.
Keywords: E32; E44; 330; Lending Standards; Deep Habits in Banking; Macroeconomic Fluctuations